Orthotic care needs in a cohort of neurological rehabilitation inpatients. (18th August 2021) - Young, Joshua; Moss, Cameron
Abstract: Aim: Orthotic management is frequently part of the rehabilitation of various neurological conditions in adults such as stroke, peripheral neuropathies, spinal cord injuries and multiple sclerosis. Despite this, there are limited data available on the implementation of orthotic care in practice. The primary aim of this study is to establish the proportion of inpatients in a mixed neurorehabilitation cohort which receive orthotic assessment and treatment. The secondary aim was to document the overall care pathway. Methods: Existing data were reviewed retrospectively. Data gathered included patient demographics such as age, gender and diagnosis, type of orthoses prescribed, number of orthotic treatment sessions required and outcome measures used. The paper was prepared in accordance with the STROBE statement for observational studies. Results: During a 6 month period, 54 patients were admitted as inpatients. Of these, 25 (46%) were referred to the orthotic service for assessment, with 23 (43%) receiving a lower limb orthosis and 19 (35%) subsequently being discharged using either an ankle-foot orthosis or knee-ankle-foot orthosis. The conditions most commonly seen were stroke (40%), incomplete spinal cord injuries (28%) and peripheral neuropathies (16%). Significant improvements were recorded at discharge using the Functional Independence Measure (FIM) and Functional Assessment Measure (FAM). Various aspects of the orthotic care process are described. Conclusions: This study suggests that orthotic treatment is needed with high frequency in a mixed inpatient neurorehabilitation cohort. In terms of service planning, these data support existing the recommendation that neurological rehabilitation centres should have good access to orthotic services. Implications for rehabilitation: Custom orthoses such as AFOs and KAFOs are frequently needed by neurological rehabilitation inpatients. Orthoses may facilitate standing and walking at an earlier stage during rehabilitation. Those responsible for neurological rehabilitation services should ensure appropriate access to orthotic services.